A comparison of formalin and GEWF in fixation of colorectal carcinoma specimens: rates of lymph node retrieval and effect on TNM staging. Issue 6 (30th November 2015) - Horne, Joanne; Carr, Norman J; Bateman, Adrian C; Kandala, Ngianga; Adams, Jody; Silva, Sónia; Ryder, Isobel
Abstract : Aims: The Royal College of Pathologists recommend that a median of at least 12 lymph nodes should be harvested during pathological staging of colorectal cancer. It is not always easy to harvest the required number, especially in patients with rectal cancer receiving neoadjuvant therapy. Lymph node revealing solutions, for example, GEWF, may improve nodal yield. GEWF is safe, cheap and easy to use. Methods: In a controlled trial, lymph node yields were compared after secondary specimen dissection following either 24 h of further fixation in formalin (n=101) or GEWF immersion (n=99). The number, size and tumour status of additional lymph nodes identified were compared between groups. Twenty-seven cases that received long-course neoadjuvant therapy were also assessed. Results: Median lymph node yield at primary dissection met national standards overall (19) but also in the long-course neoadjuvant therapy group (13). Lymph nodes were smaller in neoadjuvant cases compared with non-neoadjuvant cases (mean size range 1.3–5.6 mm vs 1.5–8.9 mm). The use of further fixation and GEWF detected more nodes at secondary dissection. The mean number of additional nodes harvested was greater with formalin (8.3) than GEWF (7.3). There was no significant difference in the mean size of the additional lymph nodes detected between groups (point estimate 1.02; 95% CI −0.58 to 2.63; p=0.211). Upstaging triggering adjunct chemotherapy occurred in 1% (2/200) of cases. Conclusions: The routine use of adjunct techniques to identify additional lymph nodes is unnecessary with underlying high-quality dissection practice. Emphasis should be placed upon education and training, spending appropriate time dissecting and ensuring specimens are sufficiently fixed beforehand.